Simulação de comportamento de ligações semirrígidas entre vigas e pilares pré-fabricados por meio de modelagem computacional - Barlati, Gustavo Braceiro (2020)
This study presents relevant aspects for the adequate use of computational models developed by the finite element method (FEM) as an instrument for investigating the behavior of precast structures, or to complement experimental tests. In order to do this, experimental tests were emulated. These tests investigated semi-rigid connections between precast beams and columns, using real-scale parts. Procedures for modeling elements on reinforced concrete were described, such as the definition of physical characteristics and constitutive models of elastic and plastic phases of materials, and an investigation of interactions between parts and definitions of contacts, presenting how to apply them on a finite element software (for this project the commercial software Abaqus was used). The conformity between numerical models and experimental tests was verified by performing comparisons of their results, such as force-displacement curves, rotation-moment, and stress-strain in the reinforcement bars. Once the convergence between models and tests is achieved, it is also realized, by means of parametric modeling, verification of the simplified method of calculating the secant stiffness and the rotation restriction factor for different negative reinforcement bars’ rates on the studied connections.